Smoking Pattern among Rural Indian Cancer Patients: A Prospective Survey - Pandey, Avinash; Singh, Anjana; Singh, Shivkant; Shahi, Heena; Kumar, Amit; Kumari, Aishwarya; Das, Anshuman (Indian Journal of Medical and Paediatric Oncology, 2020)
Background: Smoking predisposes to cancer. Prevalence and pattern of smoking among rural Indian cancer patients is unknown. Aim: The aim of the study was to estimate the prevalence of smoking in cancer patients. Objective: The objective of the study was to estimate the type of smoking and pattern in cancer patients and correlate with clinical and demographic variables through a prospective survey. Materials and Methods: All consecutive individual adult (age >18 years) patients diagnosed with any cancer and registered in the medical oncology outpatient department were enrolled for questionnaire-based survey on smoking between July 2017 and October 2017. Demographic variables were also recorded including income, education, and occupation. Frequency distribution and cross tabulation were used for the statistical analysis using SPSS version 17. Results: Of 517 cancer patients enrolled, 456 (88%) were rural. The prevalence of smoking was 125/517 (0.24, 95% confidence interval – 0.20–0.27). Among them, 67 (54%) were bidi smokers, while 58 (46%) smoked cigarette. Majority had smoking history of more than 20 years (40%), while 20% were recent smokers, <5 years. Hundred out of one hundred twenty-five (80%) patients were male, while 24/25 (96%) women smoked bidi. More than 56% of the bidi smokers were illiterate, while the majority of cigarette smokers (50%) had completed high secondary schooling. The majority of bidi (63%) and cigarette smokers (62%) had monthly income <Rs. 10,000. Almost 98% of bidi smokers and 77% of cigarette smoking population were rural. Farmers and laborers had higher prevalence of smoking, 35/96 (53%) and 28/70 (40%), respectively, while 11% of housewives were bidi smokers. Nearly 40% of head-and-neck cancer and 48% of lung cancer patients had a smoking history, with 65% and 76% being bidi smokers among them, respectively. Conclusion: One in four cancer patients smoke. Most of the smokers are illiterate with low socioeconomic profile and predominantly laborers and farmers. Bidi is the predominant type of smoking.
Keywords: Bidi; cancer; rural; smoking